Ferromagnetic Fe-substituted Cerium Oxide Nanorods: Synthesis and characterization - Alla S.K.; Devarakonda K.K.; Komarala E.V.P.; Mandal R.K.; Prasad N.K. (My University, 2025)
In this study, we have synthesized nanostructured FexCe1 − xO2 (0 ≤ x ≤ 0.5) particles by microwave refluxing method. All the samples were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), Raman, UV–vis, photoluminescence and X-ray photoelectron spectroscopy. The microstructural characterization reveals that at lower concentration of Fe (x = 0.1), the sample predominantly has spherical shape particles along with nanorods. The nanorods become prominent with increased Fe content. Further, the substitution of Fe3 + ions in CeO2 caused formation of defect states between Ce4 + conduction band and O2– valence band. These defect states or oxygen vacancies caused increase in the saturation magnetization (Ms). Even the anisotropy of the nanorods reduces the localized antiferromagnetic interaction between Fe3 + ions and hence MS value found to be increasing. © 2016 Elsevier Ltd